The effects of remdesivir on long-term symptoms in patients hospitalised for COVID-19: a pre-specified exploratory analysis - Thale D. J. Hovdun Patrick-Brown; Andreas Barratt-Due; Marius Trøseid; Anne Ma Dyrhol-Riise; Katerina Nezvalova-Henriksen; Trine Kåsine; Pål Aukrust; Inge C. Olsen; NOR Solidarity consortium (Communications Medicine)
Abstract Background There is an unmet need for treatment of long-term symptoms following COVID-19. Remdesivir is currently the only antiviral approved by the European Medicines Agency for hospitalised patients. Here, we report on the effect of remdesivir in addition to standard of care on long-term symptoms and quality of life in hospitalised patients with COVID-19 as part of the open-label randomised NOR-Solidarity trial (NCT04321616). Methods A total of 185 patients were included in the main trial, of which 118 (60%) were randomised to either remdesivir (n = 42; 36%) or a post-hoc defined control group composed of patients who received standard of care alone or standard of care with hydroxychloroquine (n = 76; 64%). Participants were given quality of life surveys to fill out to gauge their self-reported health over time (the COPD assessment test, the EQ-5D-5L and the RAND SF-36). Results Here we show that after three months, patients treated with remdesivir do not show significant improvements in stated health compared to those who were not. There are self-reported symptoms of fatigue [mean remdesivir group 2.6 (standard deviation 1.5) v control 2.1 (1.6), 95% confidence interval(CI) −1.17 to 0.15, p = 0.129], shortness of breath [3.0 (1.7) v 2.1 (1.8), 95% CI −1.53 to 0.16, p = 0.110] and coughing [1.8 (1.6) v 1.2 (1.5), 95% CI −1.3 to 0.33, p = 0.237] 3 months after randomisation assessed via the COPD Assessment Test. Conclusions Our findings indicate that treatment with remdesivir during hospitalisation does not provide any clinically relevant long-term benefit.